2008
DOI: 10.4197/islec.21-1.2
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Marketing Ethics and Its Impact on Customer Satisfaction in the Islamic Banking Industry

Abstract: Abstract. Islamic marketing ethics combines the principle of value maximisation with the principles of equity and justice for the welfare of the society. Adherence to the Islamic ethics in the Islamic banking industry can help elevate the standards of both behaviour and living of bankers and customers alike. In a rapidly changing marketing environment the need to be customer-focused has never been as important as it is today. At present where customers are becoming more demanding and increasingly mobile betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 21 publications
1
49
1
5
Order By: Relevance
“…Given today's challenging market environment and customer demands for quality services, marketers not only have to be customer-focused but also need to be perceived as Islamic by their customers (Hassan et al, 2008). A review of past literature has revealed a large volume of research in marketing that indicate ethics as among the main issues in marketing and sales (Wotruba, 1990;Piercy & Lane, 2007).…”
Section: Measure Of Islamic Relationship Marketingmentioning
confidence: 99%
See 3 more Smart Citations
“…Given today's challenging market environment and customer demands for quality services, marketers not only have to be customer-focused but also need to be perceived as Islamic by their customers (Hassan et al, 2008). A review of past literature has revealed a large volume of research in marketing that indicate ethics as among the main issues in marketing and sales (Wotruba, 1990;Piercy & Lane, 2007).…”
Section: Measure Of Islamic Relationship Marketingmentioning
confidence: 99%
“…Basically, this relates to religious aspects that promote affiliation, commitment, motivation, knowledge, and social consequences, and is believed to influence customers' confidence with the sales person (Nazlida & Mizerski, 2010). In addition, Hassan et al (2008) have advocated that Islamic ethical behaviours play a significant role in the development and maintenance of the buyer-seller relationship. This is further supported by a more recent study by Shamsudin et al (2010), in which the authors claim that Islamic ethical behaviour has promoted a positive environment in relationship marketing practice, and this naturally would lead to customer satisfaction.…”
Section: Measure Of Islamic Relationship Marketingmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been some research on marketing and advertising which can influence customers' buying behaviour (Abideen & Saleem, 2011;Gilaninia & Ghashlagh, 2012) and the selection of Islamic banks (Haron et al, 1994;Gerrard & Cunningham, 1997;Hassan et al, 2008;Haque, 2010;Adnan, 2010;Hakim et al, 2011). Similarly, other studies have indicated that there is significant relationship between effective marketing and advertising and the consumers' buying behaviour (Abideen & Saleem, 2011;Gilaninia & Ghashlagh, 2012).…”
Section: Marketing and Advertisingmentioning
confidence: 99%